Oncogenic human papillomavirus DNA in female sex workers of Bihar, India - Akhtar Parwez; Sunit Singh; Rahul Kumar; Sristy Kumari; Arun Kumar; Mohammad Ali (International Journal of Health Sciences, 2022)
Objective: Human papillomavirus (HPV) is a sexually transmitted virus which play a vital role to developing Cervical cancer. It is presumed and accepted that sexually exposed women will have occurred HPV infection at least once in their whole life. Hence, determined the actual cause of transmission of HPV infection in sexually active women with single sex partner that is married women and sexually active women with multiple sex partners that is female sex works (FSWs). Methods: A total 197 urine sample of FSWs and MW has been utilized through RT-PCR technique for HR-HPV detection. DNA extracted from urine samples and estimation and purification of DNA, used RT-PCR technique for HPV-16 and HPV-18 detection. Results: The overall prevalence of HR-HPV was detected to be 16.75% (33/197) and 83.25% (164 out 197) negative results reported in both studied subjects. The results analysis of HPV-16 and HPV-18 reveals in which prevalence of HPV-16 was 14.21% (28/197) and HPV-18 was detected 2.53% (5/197) in studied subjects in both study groups. The prevalence of HPV-16 and HPV-18 among MW was high (18.75%) and HPV-16 and HPV-18 was low (14.85%) in FSWs. It did not differ significantly of HR-HPV prevalence in MW who has single sex partner and FSWs who has multiple sex partners. Conclusion: The study indicates that oncogenic HPV prevalence did not different significantly in multiple sex partners, that is, FSWs and single sex partner, that is, MW. The probability of genital hygiene rather than multiple sexual partners stands more apt as a cause of HPV infection. This study advises to develop more awareness program about genital hygiene in women to reduce the HPV infection and can be prevented from cervical cancer. Hence, genital hygiene may be reducing the burden of HPV infection in women.